Humanitarianism from Below: Sowa Rigpa, the Traditional Pharmaceutical Industry, and Global Health. Issue 2 (17th February 2020) - Kloos, Stephan
ABSTRACT: In this article I explore, for the first time, the relationship between Sowa Rigpa (Tibetan medicine) and global health, tracing "the global" in ethical discourses and pharmaceutical innovation practices of Tibetan medical practitioners. I argue that Sowa Rigpa's engagement with the world and its global health activities outside China can be understood as a form of "humanitarianism from below, " while its industrialization in China aligns with global health in different ways. In providing new insights into recent developments of Sowa Rigpa, I aim to decenter the notion of humanitarianism and contribute to a broader understanding of global health. Abstract :